Hi Guys,
I'm a little stuck on how on to differentiate when equations involve e and ln. How would I go about differentiating y= e^x^2 ln x for instance ?
Thanks for your help.
Please use parantheses for grouping!
Which one of the following equations do you mean:
y= e^(x^2)*ln (x) ---- > $\displaystyle \displaystyle{y = e^{x^2} \cdot \ln(x)}$
y= e^((x^2)* ln (x)) ---- > $\displaystyle \displaystyle{y = e^{x^2 \cdot \ln(x)}}$
y= e^(x^(2* ln (x))) ---- > $\displaystyle \displaystyle{y = e^{x^{(2 \cdot \ln(x))}}$
You can't just take the derivative of one factor and multiply it by the derivative of the other factor. As I said, we have to use this product rule:
$\displaystyle \frac d{dx}[uv] = u\frac{dv}{dx} + v\frac{du}{dx}.$
So your answer, before simplification, should have two terms.